Instantaneous Habitable Windows in the Parameter Space of Enceladus' Ocean. Issue 11 (30th October 2021) - Higgins, Peter M.; Glein, Christopher R.; Cockell, Charles S.
Abstract: In recent years, Enceladus' subsurface ocean has become a tantalizing case study for potentially habitable conditions in an extraterrestrial ocean world. However, we still know very little about its subsurface conditions. Its oceanic composition is difficult to characterize with current data and estimates are highly dependent on model‐based interpretations which are also not yet tightly constrained. In light of these uncertainties, we consider a wide selection of the inferred parameter spaces to quantify the energy available to putative hydrogenotrophic methanogens on Enceladus in the bulk ocean at cool and elevated temperatures. We estimate the instantaneous power supply their metabolism could provide in these conditions and compare it to the expected power demands of life on Earth. To be habitable for methanogens a 273 K ocean with relatively high salt content must have pH < 10, and a relatively low salt ocean must have pH < 8 at 273 K, or pH < 9 when heated to > 360 K. Some combinations meet the power demands of exponential growth, but large swathes of the parameter space appear energetically uninhabitable. The habitability of the Enceladus ocean for methanogens appears to be a delicate balance between its temperature, pH, salinity, and concentrations of carbonates, nutrients, and dissolved gases (particularly H 2 ). Many of these parameters are co‐dependent; variation in any one of them could tip the balance into uninhabitable conditions. Further constraining these variables should be a priority for future missions to ocean worlds to enable definitive assessments of their habitability. Plain Language Summary: Observations of Enceladus in recent years have revealed tantalizing details of its potentially habitable subsurface ocean, allowing its conditions to be resolved in unprecedented detail compared to other icy moons. Still, the variation in possible parameters below its icy shell is huge, ranging from the cold bulk ocean with a pH similar to seawater on Earth to potentially scalding alkaline fluids at its depths. The ocean contains the ingredients of an ancient metabolism that is used by life on Earth by organisms known as methanogens. In this study, we explore the instantaneous habitability of Enceladus' subsurface ocean to methanogens using a range of environmental parameters informed by data from the Cassini mission and modeling. In other words, we ask: if Cassini's observations offered a "snapshot" view of the ocean, does a habitable window exist within the uncertainty of the data, without considering as‐yet unconstrained (but still important) variables such as a supply of nutrients? Some parameter combinations appear habitable, but not all the combinations are suitable for methanogens as we know them on Earth. We identify the most important drivers of habitability in Enceladus' ocean and explain how they can be better constrained by future research or space missions. Key Points: Key known drivers of the Enceladus ocean's habitability with respect to methanogens are identified and their uncertainties accounted for There is energy available for methanogens in most cases if the pH of the bulk ocean is less than 10 Instantaneous microbial power supplies imply both habitable and uninhabitable conditions are possible